The human gastroinstestinal tract microbiota in health – current knowledge summary - Prylińska-Jaśkowiak, Monika; Kożuchowski, Marcin (Journal of Education, Health and Sport, 2022)
The health of the human body is influenced by many external and internal factors, but one of the most important of them is the rich microbiota of the human body. The number of microorganism cells inhabiting the human body exceeds the number of cells that make up the human body. Several different ecosystems coexist in the human body, incl. microbiota of the skin, eye, respiratory tract, urogenital tract and gastrointestinal tract. The composition of microbiota in various parts of the human body, as well as in various parts of a given system or organ, differs significantly from one another. Detailed knowledge of the composition of the human microbiota, as well as its functions for the host organism, is a starting point for further considerations on the meaning of dysbiosis, i.e. changes in the composition of the microbiota, for changing the functioning of the microbiota-host relationship and the development of disease states. It seems that further scientific research on this topic will lead to the recognition of microbiota as a marker and diagnostic tool, and possibly a past therapeutic target for some diseases. This publication attempts to organize and summarize basic information on the human gastrointestinal tract microbiota (GIT microbiota) in health.